Sintesis polivinil alkohol tersulfonasi sebagai katalis dalam produksi metil ester: Review - Irawan, Maria Gracella; Sugih, Asaf Kleopas; Oemar, Usman; Atin, Jessica; Muljana, Henky (Jurnal Rekayasa Proses, 2022)
Sulfonated polyvinyl alcohol (PVA) can be used as a heterogeneous catalyst in esterification or transesterification reactions during methyl ester production. This catalyst with PVA support has the potential to be used commercially like Amberlyst 46. However, there are several drawbacks in the conventional methods to produce sulfonated PVA compared to Amberlyst 46. In this paper, various processes of sulfonated PVA synthesis will be discussed including the advantages and disadvantages compared to Amberlyst 46. The synthesis of sulfonated PVA catalysts can be carried out using sulfosuccinate acid reagents or other acid reagents that have sulfonic groups that act as the active sites of the catalysts. The use of sulfosuccinate acid as the reagent produces catalysts with better catalytic activity, but the resulting product is not in granule form like Amberlyst 46 and can only be used continuously for seven times. The use of chlorosulfonic acid as the reagent resulted in granular catalysts. However, the catalyst has less catalytic activity and stability, and the reagent has a relatively high environmental impact. For the synthesis performed using sulfuric acid as the reagent, no result regarding catalytic activity has been reported elsewhere. The blending of the catalyst with other polymers resulted in improvements in the thermal stability and mechanical strength of the sulfonated polyvinyl alcohol. After a careful review of the procedures, we propose blending or double cross-linking processes combined with sulfonated PVA synthesis as a promising method to increase the thermal stability and mechanical strength of the catalysts. However, it is necessary to perform further laboratory validations on the catalytic activity of the catalysts produced from the combined method because blending may reduce the acid capacity of the catalyst.